2005
DOI: 10.1093/brain/awh706
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic factor synergy is required for neuronal survival and disinhibited axon regeneration after CNS injury

Abstract: The therapeutic effects of individual neurotrophic factors (NTF) have proved disappointing in clinical trials for neuronal repair and axon regeneration. Here, we demonstrate NTF synergistic neuronal responses after a combination of basic fibroblast growth factor, neurotrophin-3 and brain derived growth factor delivered to the somata of retinal ganglion cells promoted greater survival and axon growth than did the sum of the effects of each NTF alone. Triple and not single NTF treatments potentiated regulated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
114
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(121 citation statements)
references
References 54 publications
6
114
1
Order By: Relevance
“…However, the physiological significance of Ocm has been unclear in the absence of evidence showing that it is actually expressed by inflammatory cells that infiltrate the eye after lens injury or Zymosan, or that it plays an essential role in inflammation-induced regeneration in vivo. In addition, there have been reports that factors other than Ocm can induce regeneration in this system (18)(19)(20), that depletion of macrophages or Ocm does not affect regeneration (20,21), and that Ocm is undetectable in the eye after lens injury (21). Our results contradict these latter findings.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…However, the physiological significance of Ocm has been unclear in the absence of evidence showing that it is actually expressed by inflammatory cells that infiltrate the eye after lens injury or Zymosan, or that it plays an essential role in inflammation-induced regeneration in vivo. In addition, there have been reports that factors other than Ocm can induce regeneration in this system (18)(19)(20), that depletion of macrophages or Ocm does not affect regeneration (20,21), and that Ocm is undetectable in the eye after lens injury (21). Our results contradict these latter findings.…”
Section: Discussioncontrasting
confidence: 83%
“…It remains possible, however, that CNTF could contribute to the effects of intraocular inflammation in enhancing RGC survival (20,28). The combination of NGF, NT3 and FGF2 has also been reported to promote axon regeneration in the optic nerve (18), although the cellular mechanisms and physiological significance of these findings are presently unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distinct growth factors have been identified which may affect optic nerve regeneration. A combination of fibroblast growth factor 2 (FGF2), neurotrophin 3 (NT3) and brain derived neurotrophic factor (BDNF) (Logan et al, 2006) has been reported to stimulate axonal outgrowth of RGCs. Furthermore a range of molecules have been identified, which can reduce dendrite formation, e.g.…”
Section: Optic Nerve Regenerationmentioning
confidence: 99%
“…NTs also bind to the low-affinity p75 neurotrophin receptor (p75 NTR ). NTs may strengthen their effects by cooperation both among them and with the basic fibroblast growth factor (bFGF) [3,4]. The bFGF belongs to the fibroblast growth factor (FGF) family, whose members are involved in angiogenesis, wound healing, and embryonic development [5].…”
Section: Introductionmentioning
confidence: 99%